Reflections on the Teaching of Creative Writing At the American Universities - Jamil, Adil (European Scientific Journal, ESJ, 2016)
Creative writing as an academic discipline has been contested since the very beginning of its existence at the American universities, and "backlash against it is always in full blood" (Burroway, 61). To critics, it seems to be softer, and less rigorous discipline, in comparison to other English studies (Elliott 100). Other critics describe it as the most undertheorized and in that respect the most anachronistic [field] in the entire constellation of English study (Haake, 83). Even some faculty members at English departments expressed mockery and sarcasm when the universities began recruiting creative writers to teach creative writing. For instance, a professor of English at Cornell University, who when told of the proposal to hire the novelist Vladimir Nabokov, said to do so would be like the Department of Zoology hiring an elephant (Dibble & Van Loon. April 2000). In examining critics’ negative stand, one may assume that it basically stems from two different misconceptions: first, critics seem unable or possibly unwilling to digest the idea that creative writing is a process-led, process-based discipline and its nature decrees different set of conventions and teaching techniques; second, it is more possibly that critics’ adverse stand is based chiefly upon the performances of some incompetent instructors whose ineffective performances are taken as ground for criticism. Against all odds, creative writing has continued growing and expanding incessantly and has always received strength from its popularity and ability to recruit, and all attempts to marginalize it would be doomed to failure. Unfair and rather groundless attitudes persist regardless of the acknowledged popularity. The current study is designed to show the highlights of teaching creative writing at the American universities, and then to fairly discuss this peculiar experience and gauge its validation. After surveying the current state of this ever-blooming discipline and the negative stand held by some critics, the study examines the commonalties, the shared conventions, and the ground rules of fiction writing workshops. A considerable number of essentials would be tackled such as the layout, the setting of workshop, the number of enrolled students, the requirements of completion and success, the portfolio and its contents, the role of instructor, the conduct of student author, and of student critic, and the response to peer work. The rules that govern class discussion, the instructors’ theoretical assumptions, and the methods of assessing and grading student work are also examined. The careful scrutiny of the aforementioned essentials may hone the idea that creative writing is like other disciplines, if not better; it is neither softer, nor less rigorous discipline; actually it is more demanding, more rigorous, and more orderly in comparison to other English studies. Furthermore, the study would show that every activity in the workshop stems from unspoken theoretical assumptions about whether or not writers used conventions and generic expectations. Besides, this study would spotlight the effective means and methods used by competent instructors to nurture the promising, yet still unborn, talents of young writers. In brief, this study has two goals in mind: first to bring to light the shared conventions and ground rules prevalent in organized fiction writing workshops, and second to deflate the ever-blowing adverse criticism and to show the futility and groundlessness of it.